Development and validation of point‐of‐care testing of albuminuria for early screening of chronic kidney disease. Issue 4 (16th February 2021) - Vutthikraivit, Nuntanuj; Kiatamornrak, Patcharakorn; Boonkrai, Chatikorn; Pisitkun, Trairak; Komolpis, Kittinan; Puthong, Songchan; Lumlertgul, Nuttha; Peerapornratana, Sadudee; Thanawattano, Chusak; Tungsanga, Somkanya; Praditpornsilpa, Kearkiat; Tungsanga, Kriang; et al.
Abstract: Introduction: Chronic kidney disease (CKD) is a significant global health issue. As the prevalence of renal replacement therapy (RRT) in Thailand is increasing, early detection and management of CKD is the most important step to prevent CKD progression and the need for RRT. Current diagnostic tests for CKD are non‐specific and expensive. We aimed to develop and validate antibody‐based‐albumin point‐of‐care testing (POCT) to detect patients with impaired kidney function at early stage. Methods: The prototype strip test was developed under the concept of competitive lateral flow immunochromatography assay, or strip test. Monoclonal antibodies (MAbs) to human serum albumin (HSA) were harvested from the hybridomas of spleen cells from immunized mice and mouse myeloma cells. Presence of MAbs was detected by enzyme‐linked immunosorbent assay (ELISA). Spot urine was obtained from patients with kidney disease, type I, or type II Diabetes Mellitus upon their visit at King Chulalongkorn Memorial Hospital during 2018–2019. All samples were analyzed for urine albumin with our POCT (CU microalbumin) and the other two commercial POCTs (Microalbu PHAN and MICRAL). The results were validated against standard method for urine microalbumin measurement. A urine microalbumin concentration of less than 20 ug/ml was defined as normal. The sensitivity, specificity, and predictive values were calculated in comparison with the standard laboratory method. Result: A total of 100 adult patients were included. CU microalbumin had a sensitivity of 86%, a specificity of 94%, and a positive predictive value of 96%. Our POCT showed good correlation with the laboratory results. Conclusion: CU microalbumin correlated well with the standard method for quantitative measurement of urine albumin. Therefore, it has the potential for early screening of CKD, especially in primary health care facilities in resource limited settings.